2016
DOI: 10.1371/journal.pone.0150142
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Associated Factors of Physical Activity among Adolescents in Nigeria

Abstract: IntroductionUnderstanding the context where adolescents’ physical activity (PA) takes place could impact a more targeted approach to implement PA promotion and interventions in Africa. However, standardized data on adolescents’ PA behaviour is lacking in Nigeria. We described PA patterns in the various domains (home, school, transport, leisure-time) and intensity categories (light-intensity PA, moderate- to vigorous- intensity physical activity [MVPA] and total PA), and their associations with sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
93
1
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(112 citation statements)
references
References 51 publications
11
93
1
2
Order By: Relevance
“…The change was necessitated by new evidence that was reported for a group of Nigerian adolescents. 15 While it was reported in earlier studies that about 30%-75% of children and youth in Nigeria continue to engage in different forms of PA, [12][13][14][15] according to the current data, 15 only 37% of a representative sample of 1006 secondary school adolescents in urban northeastern Nigeria appear to meet the international guidelines of engaging in at least 60 minutes of moderate-to-vigorous physical activity (MVPA) daily, based on self-reported PA. 15 Active Play and Leisure: C Active Play and Leisure was assigned a grade of C, which showed a slight improvement over the C-in the 2013 Nigerian Report Card. As previously observed, the proportion of active play and leisure PA among Nigerian children and youth varied between 12% and 70%.…”
Section: Overall Physical Activity: Dmentioning
confidence: 99%
See 1 more Smart Citation
“…The change was necessitated by new evidence that was reported for a group of Nigerian adolescents. 15 While it was reported in earlier studies that about 30%-75% of children and youth in Nigeria continue to engage in different forms of PA, [12][13][14][15] according to the current data, 15 only 37% of a representative sample of 1006 secondary school adolescents in urban northeastern Nigeria appear to meet the international guidelines of engaging in at least 60 minutes of moderate-to-vigorous physical activity (MVPA) daily, based on self-reported PA. 15 Active Play and Leisure: C Active Play and Leisure was assigned a grade of C, which showed a slight improvement over the C-in the 2013 Nigerian Report Card. As previously observed, the proportion of active play and leisure PA among Nigerian children and youth varied between 12% and 70%.…”
Section: Overall Physical Activity: Dmentioning
confidence: 99%
“…16 But a new study utilizing self-reported PA data indicates that secondary school adolescents in urban northeastern Nigeria, on average, spent about 1 hour daily in active play and leisure (about 11% of daily PA). 15 The availability of this new evidence 15 that documented the amount of time spent on active play by children earned the indicator a slight increase in grade from C-to a C. Evidence is available that among Nigerian children and youth, active play and leisure is influenced by gender and socioeconomic disparities. Boys from families with high socioeconomic status are more likely to engage in active play and leisure than their peers from low socioeconomic status.…”
Section: Overall Physical Activity: Dmentioning
confidence: 99%
“…One previous study showed positive associations between SES indicators (mother's education level and type of school) and physical activity (which was defined as participating in moderate-to-vigorous physical activity >300 min/week) [13]. Another study conducted on Nigerian adolescents reported, that leisure-time physical activity, active transportation, moderate-intensity activity and total physical activity were associated with higher SES [38]. Moreover, one study also showed the same results, where participants who participated in at least 60 min/day of moderate-to-vigorous physical activity, were categorized in the highest socioeconomic class.…”
Section: Discussionmentioning
confidence: 99%
“…Tem sido demonstrado que rapazes são mais ativos que moças em diversos contextos da atividade física 24,25 . Similar ao verificado neste estudo, moças nigerianas também foram menos ativas no deslocamento que rapazes, mas não apenas nesse domínio, elas também foram menos ativas para atividade física no lazer e total 24 .…”
Section: Discussionunclassified
“…Similar ao verificado neste estudo, moças nigerianas também foram menos ativas no deslocamento que rapazes, mas não apenas nesse domínio, elas também foram menos ativas para atividade física no lazer e total 24 . Resultado similar foi identificado em estudo com adolescentes alemães para padrões de atividade física, por domínio, utilizando-se de acelerometria 25 .…”
Section: Discussionunclassified